The Effect of Selected Poor Item-Writing Practices on Test Difficulty, Reliability and Validity A Replication - Schmeiser, Cynthia Board; Whitney, Douglas R. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
Violations of four selected principles of writing multiple-choice items were introduced into an undergraduate religion course mid-term examination. Three of the flaws significantly increased test difficulty. KR-sub-20 values were lower for all of the tests containing the flawed items than for the "good" versions of the items but significantly so in only one of four comparisons. The reductions in reliability were equivalent to those expected to result from shortening the "good" test by 28 to 71 percent. Concurrent validity (correlation of experimental test scores with the midterm test of similar content) was lower in all four cases, but significantly so in only one of four cases. The reductions in validity were equivalent to those expected to result from shortening the test by 47 to 77 percent. (Author)
ERIC Note: Paper presented at American Educational Research Association Meeting (New Orleans, Louisiana, February 25-March 1, 1973).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Item Analysis; Multiple Choice Tests; Research Reports; Test Construction; Test Reliability; Test Results; Test Validity